Evaluation of Bioactive Composition and Phytochemical Profile of Macroalgae Gracilaria edulis and Acanthophora spicifera from the Banda Aceh Coast, Indonesia - Said Ali Akbar; Hasan, Muhammad (Science & Technology Asia, 2024)
This study aimed to examine the metabolite profiles and phytochemical content of Gracilaria edulis and Acanthophora spicifera along the coast of Banda Aceh in Indonesia. The three attributes observed by this study were phytochemical composition, antioxidant scavenging, and in vivo metabolite profile by the use of Gas Chromatography-Mass Spectrometry (GC-MS), antioxidant activity test, and Fourier Transform Infrared (FTIR) characterization, respectively. Extracts from both G. edulis and A. spicifera demonstrated high scavenging capability, with inhibition values of 42.59% and 39.81%, respectively. In both species, the GC-MS methodology was shown to be a quick, sensitive, and trustworthy way to monitor individual components and the entire chemical composition. In G. edulis, there were 29 phytochemical compounds, whereas in A. spicifera, there were 26 compounds. The ethanol extracts of G. edulis and A. spicifera were then subjected to an FTIR spectrum analysis. These findings at 3352 cm-1, 1654 cm-1, and 1019 cm-1 proved that alkanes, alkenes, and hydroxyl groups were present, corresponding to several compounds in the GC-MS measurement results. G. edulis and A. spicifera are potential antibacterial agents; the bioactive compounds conferring this activity are heptadecane, hexadecanoic acid, and other ester derivatives.